Evaluation of antibacterial action of photosensitizer solution activated by diode lamp and three intracanal medicaments (in vitro study) - Hirais, Mohammed C; Al-Huwaizi, Hussain F (Journal of Baghdad College of Dentistry, 2013)
Background: The elimination of the microorganisms from the root canal systems, an important step for the successful root canal treatment. This study was conducted to evaluate the antibacterial effectiveness of the photoactivated disinfection by using the toluidine blue O and a low- energy light emitting diode (LED) lamp .Materials and method: Sixty single rooted extracted teeth were decoronated, instrumented, irrigated, sealed at the apex and contaminated with endodontic anaerobic bacteria for 7 days to form biofilms in prepared root canals. Group I. Twelve teeth were medicated by photosensitizer (toluidine blue O) solution activated by diode lamp (FotoSan; CMS Dental, Copenhagen, Denmark).Group II. Twelve teeth were medicated by the tricresol formalin. Group III. Twelve teeth were medicated by the camphorated monochlorophenol (CMCP). Group IV. Twelve teeth were medicated by calcium hydroxide (Ca(OH)2) paste. Group V. Without the intracanal medication (control group). The bacterial swabs were taken before and after medication and following the photoactivated disinfection procedure immediately and after 7days. The canal contents were swabbed by paper points inserted to the root canals, serially diluted and cultured on blood agar. Survival fractions were calculated by counting colony-forming units.Result: Treatment of the root canals with PAD (fotosan) caused a high significant reduction of the bacterial count, resulting in a 96.39% elimination of root canal bacteria, followed by root canal treated by tricresol formalin (group II),then CMCP (group III) and Ca(OH)2 (group IV) respectively.Conclusion: Light activated disinfection possesses potent antibacterial action against the anaerobic bacteria cultivated in root canals.